Visible light assisted Fenton type degradation of methylene blue by admicelle anchored alumina supported rod shaped manganese oxide. (August 2020) - Biswas, Subhadeep; Pal, Anjali
Graphical abstract: Highlights: A new Fenton type MnOx catalyst was developed for degradation of methylene blue. The catalyst was anchored on the surfactant bilayer supported on alumina. Methylene blue degradation occurred in fully adsorbed condition in the solid supported micelle. The degradation efficiency was enhanced in presence of visible light. Under optimized condition ∼ 92 % decolourization was achieved. Abstract: Manganese oxide (MnOx ) nanorods supported on surfactant-modified alumina (SMA), synthesized by the redox co-precipitation method are employed as a heterogeneous photo-Fenton catalyst for degradation of methylene blue (MB) in presence of hydrogen peroxide (H2 O2 ). The uniqueness of the work is that the admicellar support of sodium dodecyl sulfate (SDS), an anionic surfactant, on base material alumina has been utilized to host both the catalyst MnOx and the target pollutant MB. The catalyst is characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), UV–vis diffuse reflectance spectra (DRS), particle size analysis and X-ray photoelectron spectroscopy (XPS). The influence of operational parameters, such as initial pH, catalyst dose, H2 O2 concentration, the intensity of visible light and initial concentration of MB has been investigated. The catalytic performance is evaluated in terms of MB decolorization. The reproducibility of the results and reusability of the catalyst is also checked. The turnover number (TON) and turnover frequency (TOF) of the catalyst are found to be 0.068 moles of MB per mole of Mn and 2.55 × 10 −6 moles of MB /mole of Mn/s. The efficiency of the catalyst to generate hydroxyl radicals under visible light is confirmed using terephthalic acid fluorescence probing technology. Under optimized conditions ∼92 % decolourization of MB was achieved using the as-developed catalyst. The main degradation intermediates were identified by ESI-MS analysis to propose a possible degradation pathway of MB.